1988
DOI: 10.3109/10826088809039206
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Patterns and Abstinence Among the Elderly

Abstract: For almost a decade the research literature has reflected both the scarcity of new knowledge regarding alcohol use or abuse among the elderly and the need to address the problem. Current theoretical perspectives on probable trends of alcohol-related problems among older persons include historical-cohort prediction, biological and clinical geriatric expectations, and sociocultural-economic expectations. These theoretical perspectives are frequently in opposition to each other and are largely untested with appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 7 publications
7
13
2
Order By: Relevance
“…Consistent with Douglass et al's (1988) and Stall's (1987) suppositions, we showed in previous research an association between overall health burden and lower alcohol consumption, and fewer drinking problems, at 10-and 20-year follow-ups (Moos et al, 2009). We showed also that baseline drinking beyond recommended guidelines, smoking, and heavier reliance on avoidance coping foreshadow within-individual decline in alcohol consumption during "early" late life (i.e., from about age 60 to about age 70; Brennan et al, 2010).…”
Section: Predictors Of Late-life Drinking Trajectoriessupporting
confidence: 64%
See 2 more Smart Citations
“…Consistent with Douglass et al's (1988) and Stall's (1987) suppositions, we showed in previous research an association between overall health burden and lower alcohol consumption, and fewer drinking problems, at 10-and 20-year follow-ups (Moos et al, 2009). We showed also that baseline drinking beyond recommended guidelines, smoking, and heavier reliance on avoidance coping foreshadow within-individual decline in alcohol consumption during "early" late life (i.e., from about age 60 to about age 70; Brennan et al, 2010).…”
Section: Predictors Of Late-life Drinking Trajectoriessupporting
confidence: 64%
“…Few studies have examined biological, psychological, and social factors proposed by Douglass et al (1988) and Stall (1987) to infl uence late-life drinking trajectories. With regard to biological infl uences, older men identify health problems as a key reason that they cut down on or quit drinking (Stall, 1986b;Walton et al, 2000).…”
Section: Predictors Of Late-life Drinking Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of alcohol problems in elderly patients related to 2 diagnostic criteria: a positive CAGE questionnaire (2 points or more) and an alcohol-related discharge diagnosis. 24,[27][28][29][30][31]. In our study a very statistically significant association was found between higher alcohol use, higher educational level and higher family income.…”
Section: Discussionsupporting
confidence: 48%
“…Lower alcohol use in older age groups has been observed in several cross-sectional studies (Douglass et al, 1988;McKim and Quinlan, 1991). However, one longitudinal study from the US found an increase over time in the mean alcohol intake of those who drank in all age groups (Gordon and Kannel, 1983).…”
Section: Introductionmentioning
confidence: 99%